Ultra-Violet Induced Biochemical Changes in an Invasive Weed and their Implications for Plant-Biocontrol Agent Interactions - Barrett DP; Subbaraj AK; Wargent JJ; Minor MA; Peterson P; Lun DJ; Clavijo McCormick A (Springer Science+Business Media, LLC, 2026)
Introducing insect biocontrol agents sourced from a plant’s native range is an effective, sustainable management strategy for invasive plants. However, not all biocontrol programmes achieve the desired outcome because control agents either fail to establish or are ineffective. Heather beetle Lochmaea suturalis (Coleoptera: Chrysomelidae), introduced from the United Kingdom (UK) to New Zealand (NZ) to control the invasive shrub Calluna vulgaris (heather), was difficult to establish and achieved poor population growth rates and expansion relative to its conspecifics in its native UK range. Poor performance in biocontrol is often attributed to various abiotic or biotic factors but seldom considers alterations to a target plants biochemical phenotype. A recent study revealed, heather has a significantly different biochemical profile in NZ compared with the UK, between which there is considerable difference in ultra-violet (UV) radiation. UV is known to drive plant biochemical change, including defensive secondary metabolites and we hypothesized that this factor could enhance heathers’ defensive capability leading to poor biocontrol agent performance. Testing this hypothesis involved exposing heather plants to 20% and 95% UV attenuating screens and using metabolomics to measure plant secondary metabolite responses. Our results demonstrate significant alterations to many compounds derived from the shikimate-phenylpropanoid pathway. However, a bioassay revealed no impact on prepupal weight or larval survival of the biocontrol agent L. suturalis. We discuss and explore possible reasons for this outcome, the magnitude and impact of UV-induced biochemical changes on plant-insect interactions and the potential of metabolomics to support weed biocontrol.
Keywords: Biochemical phenotype; Invasive plants; Metabolomics; Ultra-violet; ࣧBiocontrol